2008
DOI: 10.1634/stemcells.2008-0777
|View full text |Cite
|
Sign up to set email alerts
|

1,4,5-Inositol Trisphosphate-Operated Intracellular Ca2+ Stores and Angiotensin-II/Endothelin-1 Signaling Pathway Are Functional in Human Embryonic Stem Cell-Derived Cardiomyocytes

Abstract: On the basis of previous findings suggesting that in human embryonic stem cell-derived cardiomyocytes (hESC-CM) the sarcoplasmic reticulum Ca 2؉ -induced release of calcium machinery is either absent or immature, in the present study we tested the hypothesis that hESC-CM contain fully func-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 29 publications
(48 reference statements)
1
55
0
Order By: Relevance
“…[Ca 2ϩ ] i transients and contractions were measured by means of Fura-2 fluorescence and video edge detection, respectively, routinely used in our laboratory (Dolnikov et al, 2006;Sedan et al, 2008 Measuring Intercellular Coupling by Lucifer Yellow Transfer. The scrape-loading technique was used to evaluate the degree of gap junctional intercellular communication (Kavanagh et al, 1987).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[Ca 2ϩ ] i transients and contractions were measured by means of Fura-2 fluorescence and video edge detection, respectively, routinely used in our laboratory (Dolnikov et al, 2006;Sedan et al, 2008 Measuring Intercellular Coupling by Lucifer Yellow Transfer. The scrape-loading technique was used to evaluate the degree of gap junctional intercellular communication (Kavanagh et al, 1987).…”
Section: Methodsmentioning
confidence: 99%
“…Human embryonic stem cells (hESC) from clone H9.2 were grown on mouse embryonic fibroblast feeder, and embryoid bodies prepared as described previously (Sedan et al, 2008). The contracting areas mostly composed of cardiomyocytes were carefully dissected out by a microscalpel, and transferred to gelatin-coated 30-mm-diameter glass slides suitable for fluorescent measurements (Thermo Fisher Scientific).…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation
“…The electrophysiological properties were shown to be similar to mature differentiated cells in regard to ion channels and ionic currents [3,4]. The hESC-derived cardiomyocytes expressed a large sodium current density and the action potential was shortened by L-type Ca channel blockade.…”
Section: Stem Cells and Developmentmentioning
confidence: 88%
“…This verified the functionality of IP 3 R-channels in these cells. In H9.2 hESCs, immunostaining indicated that both IP 3 R1 and IP 3 R2 were expressed in hESC-dervied CMs (Sedan et al, 2010;Sedan et al, 2008); and the expression of IP 3 R2 was shown to gradually decline with maturation as revealed by quantitative RT-PCR (Satin et al, 2008). The expression of IP 3 R was also tested during development in vivo; its mRNA was first measured and detected as early as E5.5 in mouse embryos; it was present at high levels by E8.5 and continued to increase until E16.5 when its level started to drop (Rosemblit et al, 1999).…”
Section: Regulation Of Intracellular Calcium Level By Ligand-operatedmentioning
confidence: 99%